2013
DOI: 10.1002/cpdd.9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trastuzumab Emtansine (T‐DM1) on QT Interval and Safety of Pertuzumab Plus T‐DM1 in Patients With Previously Treated Human Epidermal Growth Factor Receptor 2–Positive Metastatic Breast Cancer

Abstract: Trastuzumab emtansine (T-DM1) is an antibody-drug conjugate in development for human epidermal growth factor receptor 2 (HER2)-positive cancer. Drugs in development are generally tested for their effects on QT interval, prolongation of which is associated with the potentially fatal arrhythmia torsades de pointes. In addition, an association between left ventricular dysfunction and other HER2-directed agents has been documented. This multicenter, phase 2 study, TDM4688g, assessed the safety and pharmacokinetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 38 publications
(87 reference statements)
1
29
0
1
Order By: Relevance
“…18 Moreover, T-DM1 had no clinically significant effect on the corrected QT interval in a dedicated phase II study of patients with previously treated HER2-positive MBC. 30 The overall safety profile of T-DM1 in EBC was also similar to that seen in phase III studies of T-DM1 in MBC, with the most commonly reported grade Ն 3 AEs being thrombocytopenia (8.1%), increased AST (7.4%), and increased ALT (7.4%). The corresponding rates in the EMILIA trial were 12.9%, 4.3%, and 2.9%, respectively.…”
Section: ‫ء‬mentioning
confidence: 54%
“…18 Moreover, T-DM1 had no clinically significant effect on the corrected QT interval in a dedicated phase II study of patients with previously treated HER2-positive MBC. 30 The overall safety profile of T-DM1 in EBC was also similar to that seen in phase III studies of T-DM1 in MBC, with the most commonly reported grade Ն 3 AEs being thrombocytopenia (8.1%), increased AST (7.4%), and increased ALT (7.4%). The corresponding rates in the EMILIA trial were 12.9%, 4.3%, and 2.9%, respectively.…”
Section: ‫ء‬mentioning
confidence: 54%
“…All study designs were approved by independent ethics committees and conducted in accordance with the Declaration of Helsinki; all patients provided written informed consent [4, 5, 810, 13, 15]. …”
Section: Methodsmentioning
confidence: 99%
“…117,118,165 Similarly, pertuzumab has not shown QTc effects. 115,116 Bevacizumab has been used alone or in combination with other TKI and other chemotherapeutic agents without causing QTc prolongation, despite its cardiotoxicity potential. [166][167][168][169]…”
Section: Small-molecule Tyrosine Kinase Inhibitorsmentioning
confidence: 99%